2016
DOI: 10.4049/jimmunol.1600974
|View full text |Cite
|
Sign up to set email alerts
|

A 33D1+ Dendritic Cell/Autoreactive CD4+ T Cell Circuit Maintains IL-2–Dependent Regulatory T Cells in the Spleen

Abstract: Phenotypically and functionally diverse regulatory T cell (Tr cell) subsets populate lymphoid and non-lymphoid tissues where their maintenance and function are governed by unique homeostatic signals. Whereas Tr cells resident in non-lymphoid tissues depend on continual TCR signaling for their survival and function, phenotypically naïve Tr cells occupying secondary lymphoid organs (SLOs) are largely supported by paracrine Il-2 signaling. Crucially, the absence of either of these distinct Tr cell subsets results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 62 publications
3
10
0
Order By: Relevance
“…3A). This is consistent with a central role for cDC2 in interaction with Treg cells [9]. Along with the increase in activated DCs, the anti-IL-2 treated mice also showed enhanced proliferation of the Foxp3 -CD44 + CD4 + and CD44 + CD62L + CD8 + Teff cell populations as assessed by Ki67 staining (Fig.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…3A). This is consistent with a central role for cDC2 in interaction with Treg cells [9]. Along with the increase in activated DCs, the anti-IL-2 treated mice also showed enhanced proliferation of the Foxp3 -CD44 + CD4 + and CD44 + CD62L + CD8 + Teff cell populations as assessed by Ki67 staining (Fig.…”
Section: Resultssupporting
confidence: 83%
“…Whereas neutralization of IL-2 blocked all pSTAT5 as expected, surprisingly Treg cells from animals treated with PC61 N297Q maintained normal levels of pSTAT5, and even treatment with PC61 2a had only a modest impact of the frequency of pSTAT5 + Treg cells ( Fig 4A). The pSTAT5 staining we observed in the treated animals does not simply reflect prolonged IL-2 signaling that occurred prior to treatment initiation, as we have previously shown that injection of IL-2 antibodies as little as 30 minutes prior to sacrifice ameliorates all detectable pSTAT5 in Treg cells [9]. Treatment with PC61 N297Q or PC61 2a also did not redirect IL-2 to effector cells, as the gMFI of pSTAT5 in both NK cells and CD44 + CD62L + CD8 + Teff was not increased by any of the treatments ( Fig S2A).…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…33D1+ DCs not only induced Th0 cells to Th2 cells, but also influenced the frequency and function of Treg cells. The frequency and function of IL-2–dependent Treg cells depends on the presentation of MHC II–restricted autoantigens to self-reactive CD4+ T cells via 33D1+ DCs ( Stolley and Campbell, 2016 ).…”
Section: Discussionmentioning
confidence: 99%